2019
DOI: 10.1371/journal.pone.0215749
|View full text |Cite|
|
Sign up to set email alerts
|

Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) in Cameroon: Case study on its distribution, damage, pesticide use, genetic differentiation and host plants

Abstract: Maize farmers in sub-Saharan Africa recently experienced unusual damage in their farms, attributed to the fall armyworm (FAW) Spodoptera frugiperda (J. E. Smith). This pest was first recorded in Africa in 2016, but detailed information on its distribution and damage and farmer’s response in invaded areas are largely lacking. In this study, we determined FAW distribution, genetic diversity, host plants, crop damage, and farmers’ responses. S . frugiperda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 43 publications
1
30
0
1
Order By: Relevance
“…In addition, as a pure leaf feeder, FAW larvae produced higher leaf damage and dispersal potential than stemborers. The devastating character in maize fields of FAW has been reported in several studies (Goergen et al, 2016; Srinivasan et al, 2018; Fotso Kuate et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, as a pure leaf feeder, FAW larvae produced higher leaf damage and dispersal potential than stemborers. The devastating character in maize fields of FAW has been reported in several studies (Goergen et al, 2016; Srinivasan et al, 2018; Fotso Kuate et al, 2019).…”
Section: Discussionmentioning
confidence: 81%
“…It has also displaced Chilo orichalcociliellus Strand in the coastal region of Kenya (Ofomata et al, 1999) and may gain an advantage over B. fusca and S. calamistis in the utilization of maize (Mwalusepo et al, 2015; Ntiri et al, 2016). Recently, the fall armyworm (FAW), Spodoptera frugiperda (JE Smith) (Lepidoptera: Noctuidae), invaded sub‐Saharan Africa, where it has seriously limited maize yields (Goergen et al, 2016; Cock et al, 2017; Fotso Kuate et al, 2019). Recent observations indicate that it closely interacts with maize stemborer communities (Sokame et al, 2020) and might also displace the stemborers.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the FAW always hides inside the stem of maize, this makes the insecticide much less effective. Although many pesticides are less harmful to the environment and humans, all these factors can lead the sublethal effects, which possibly help the FAW to evolve resistance against the pesticides 2527 . An effective compensating management for insecticides is the use of Bacillus thuringiensis (Bt) toxins produced by the by the bacterium.Bt plants have been proved fatal to many insect pests, including the FAW 2830 .…”
Section: Introductionmentioning
confidence: 99%
“…Although some research reported the resistance of FAW to Bt maize 29,30 , multiple genes or new gene with more or new Bt toxin expressed are still thought to have a good performance for resisting the FAW 29,30 . Biological control, including the, introduction of natural enemies and using companion cropping system 19,21,25,31,32 , is also an effective way to resist the FAW.…”
Section: Introductionmentioning
confidence: 99%
“…UGF adalah ngengat yang dapat bermigrasi dan bersifat polifag sehingga resiko penyebarannya sangat tinggi (Goergen et al 2016). Berasal dari wilayah tropis belahan barat Amerika Serikat dan Argentina, UGF kemudian menyebar ke wilayah Afrika dan akhirnya terdeteksi di Asia (Kuate et al 2019;Ma et al 2019). UGF juga dilaporkan sebagai hama utama pada beberapa tanaman kelompok Poaceae lainnya, seperti padi, tebu, gandum, dan sorgum (Yu et al 2003;Goergen et al 2016).…”
Section: Pendahuluanunclassified